Study of Juvenile Justice Act and System in India: Exploring the Causes and Solutions of Juvenile Delinquency in India (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Juvenile delinquency is a genuine offense and it is detrimental for the social request in any nation. There is a pattern of increment in juvenile crimes world-over, with increasingly more association of the adolescent in violent crimes. India demonstrates comparative trends of expanding rate of violent crimes carried out by the juveniles. It is an intense worry for the country and answers for end the issue should be looked for all around cautiously. Indian lawful system and legal executive has reacted to these trends and has acquired a few amendments the laws pertaining to juvenile justice in India. This paper goes for taking a gander at the reasons for juvenile delinquency and clarifications given by researchers from different fields to clarify the issue. The investigation of factual data accessible at authority destinations demonstrates expanding inclusion of the juveniles in grievous crimes. To contain the issue of juvenile delinquency in India, the Act pertaining to Juvenile Delinquency has been altered and now preliminary of juveniles associated with offensive crimes is held as adults.